Vera Nemtchinova [i.e.Nemchinova], V. Grigorieff, Lubov Tchernicheva, Serge Grigorieff and Michel Panaieff, Bellevue Hill, New South Wales, 1940 - Repin, Ivan Dmitrievich, 1888-1949 (1940)
Portraits of Russian ballet dancers and ballerinas identified from left to right.
Title devised by cataloguer based on information from acquisition documentation.
Part of the collection: The Original Ballet Russe, members and performances, Sydney, 1940.
Also available online
Donated by George D. Repin, 2006.
Keywords: Original Ballet Russe -- Photographs; Ballet dancers -- New South Wales -- Bellevue Hill -- Portraits; Ballerinas -- New South Wales -- Bellevue Hill -- Portraits; Ballet dancers -- Soviet Union -- Portraits; Ballets Russes in Australia; Ballet dancers